2009
DOI: 10.2353/ajpath.2009.080180
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Kinase Cδ-Dependent Protein Kinase D Pathway Modulates ERK1/2 and JNK1/2 Phosphorylation and Bim-Associated Apoptosis by Asbestos

Abstract: Inhalation of asbestos and oxidant-generating pollutants causes injury and compensatory proliferation of lung epithelium, but the signaling mechanisms that lead to these responses are unclear. We hypothesized that a protein kinase (PK)C␦-dependent PKD pathway was able to regulate downstream mitogen-activated protein kinases, affecting pro-and anti-apoptotic responses to asbestos. Elevated levels of phosphorylated PKD (p-PKD) were observed in distal bronchiolar epithelial cells of mice inhaling asbestos. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 70 publications
(102 reference statements)
0
28
0
Order By: Relevance
“…Since activation of ERK1/2 is increased endogenously in human MM tissues (59), and dysregulation of the Ras/Raf/MEK/ERK cascade occurs in many cancers, a variety of synthetic MEK and tyrosine kinase inhibitors may be useful in multi-drug therapeutic regimens. For example, we have recently shown that ERK 1/2 governs cell survival in lung epithelial cells via degradation of the pro-apoptotic, BH3-only protein, Bim EL (58), which antagonizes the pro-survival Bcl-2 family member, Mcl-1, an effective target of a BH3 mimetic in B-RAF mutant human tumors (60). In these latter studies, use of a MEK inhibitor and the BH3 mimetic, ABT-737, caused synergistic effects on apoptosis and antitumor activity (60).…”
Section: Future Goals and Translational Approaches To Inhibit Asbestomentioning
confidence: 99%
See 1 more Smart Citation
“…Since activation of ERK1/2 is increased endogenously in human MM tissues (59), and dysregulation of the Ras/Raf/MEK/ERK cascade occurs in many cancers, a variety of synthetic MEK and tyrosine kinase inhibitors may be useful in multi-drug therapeutic regimens. For example, we have recently shown that ERK 1/2 governs cell survival in lung epithelial cells via degradation of the pro-apoptotic, BH3-only protein, Bim EL (58), which antagonizes the pro-survival Bcl-2 family member, Mcl-1, an effective target of a BH3 mimetic in B-RAF mutant human tumors (60). In these latter studies, use of a MEK inhibitor and the BH3 mimetic, ABT-737, caused synergistic effects on apoptosis and antitumor activity (60).…”
Section: Future Goals and Translational Approaches To Inhibit Asbestomentioning
confidence: 99%
“…The induction of apoptosis by asbestos, an event that can lead to compensatory cell proliferation, and the importance of apoptosis in therapeutic approaches for eradication of MM and lung cancer cells have been widely studied and appear multi-faceted. For example, several pathways including: (1) an intrinsic or mitochondriaregulated pathway that may be p53 or protein kinase C dependent (52-54); (2) extrinsic pathways induced by death-receptor ligands such as TNF-a or FasL (55); and (3) cell signaling via AKT, prolonged activation of ERKs, and other MAPKs (40,(56)(57)(58) have been documented by asbestos and chemotherapeutic drugs in mesothelial cells, MM cells, and lung epithelial cells in vitro. In these studies, oxidative stress appears to be a central mechanism in the induction of apoptotic pathways triggered by asbestos fibers.…”
Section: Pro-apoptotic Mechanisms Of Asbestosmentioning
confidence: 99%
“…113͒ and increased activity of the antiapoptotis moleculae Bcl-X L ; 114 and ͑iii͒ compensatory proliferation pathways mediated by prolonged activation of AKT and MAPKs. [115][116][117] MPM cells are known to produce collagen and matrix metalloproteinases as well as inflammatory cells and cytokines. 118,119 The latter acts as tumor own nutrients and facilitate matrix interactions to provide a supportive environment.…”
Section: Molecular Basis Of Pleural Mesothelial Transformationmentioning
confidence: 99%
“…Many studies suggest that both ERK1 and ERK2 compete for upstream mitogen-activated protein kinase kinases (MEK1/2) and other substrates (11). Moreover, the intensity and duration of ERK signaling, intracellular compartmentalization of phosphorylated (activated) ERKs (12), substrate specificity, and downstream consequences of ERK signaling, including activation of selected transcription factors, may determine phenotypic and functional cell outcomes (13,14). Activation of these cascades by asbestos fibers may play a role in initial cell injury, as well as compensatory mesothelial cell proliferation that favors survival of genetically altered cells in carcinogenesis.…”
mentioning
confidence: 99%